Five-photon absorption upconversion lasing from on-chip whispering gallery mode. Issue 10 (4th March 2020) - Huang, Ying; Zhu, Hai; Zheng, Huying; Tang, Ziying; Dong, Jianwen; Su, Shichen; Shen, Yan; Gui, Xuchun; Deng, Shaozhi; Tang, Zikang
Abstract : We demonstrated for the first time low-threshold whispering-gallery mode upconversion lasing through five-photon absorption enhanced by on-chip microcavities at room temperature. Abstract : In the progress of ultrafast optics, nonlinear interactions between light and matter are very important in scientific and technical fields. In particular, the high-order nonlinear effect induced by multi-photon absorption (MPA) upconversion lasing has injected new impetus into the research on short-wavelength laser sources. Here, we report the realization of amplified spontaneous emission (ASE) by MPA simultaneously in an epitaxy thin film. In addition, by virtue of the excellent optical confinement of cylindrical microcavities with high Q (∼4 × 10 3 ) on-chip, we demonstrated, for the first time, low-threshold upconversion lasing of five-photon absorption enhanced by a microcavity at room temperature. The resonant whispering-gallery mode (WGM) distribution in cylindrical microcavities was simulated comprehensively by the finite difference time domain (FDTD) method. We found that the high-order nonlinear optical process could be significantly enhanced in the microcavity with an increase in the lifetime of radiation photons.